ESG Disclosure, Firm Size, Leverage, and Firm Value: Evidence from Indonesia’s Food and Beverage Sub-Sector (Pusat Riset dan Inovasi Nasional, 2026)
This research seeks to assess how ESG reporting, the size of a company, and debt levels affect its overall value in companies within the food and beverage subsector listed on the Indonesia Stock Exchange. The approach taken in this study is targeted sampling, which produced 150 observations from 50 companies during the 2022–2024 period. The data analysis process was carried out using panel data regression analysis with the assistance of EViews 12 software. The findings of this study show that ESG disclosure has a negative and insignificant effect on firm value, firm size also has a negative and insignificant effect on firm value, while leverage has a positive and significant effect on firm value. It can be concluded that, in relation to the food and drink segment within Indonesia between 2022 and 2024, the management of capital structure through leverage is a more important factor in increasing firm value compared to ESG disclosure and firm size..